An Exploration of Prevalence and Associated Factors of Nonal-Coholic Fatty Liver Disease in the Taiwanese Police Service - CT Hsu; HC Shih; TH Lin; WH Chiu; TH Tung (Tehran University of Medical Sciences, 2011)
Background: The purpose of this study was to explore any gender-related differences in prevalence of and condition-associated factors related to non-alcoholic fatty liver disease (NAFLD) amongst police population in Taipei, Taiwan.Methods: We studied a total of 1016 healthy adults with police work (972 males and 44 females) voluntarily admitted to physical check-up between January 2006 and December 2006. Blood samples and ultrasound-proved fatty liver sonography results were collected.Results: The prevalence of NAFLD for this sub-population was found to be 52.2%, the prevalence revealing a statistically significant decrease with increasing population age (P<0.001). Males exhibited a greater prevalence of NAFLD than did females (53.6% vs 20.5%, P<0.0001). Using multiple logistic regression analysis, in addition to male gender, an older age, higher BMI, higher ALT, presence of hyperuricemia, hypercholesterolemia, and hypertriglyceridemia were the significant factors associated with NAFLD. Gender-related differences as regards associated factors were also revealed. For males, hyperuricemia (OR=1.35, 95%CI: 1.07-1.86), higher ALT (OR=2.31, 95%CI: 1.50-3.56), hypercholesterolemia (OR=1.33, 95%CI: 1.01-1.82), and hypertriglyceridemia (OR=1.55, 95%CI: 1.01-2.37) were significantly related to NAFLD but these were not so for females.Conclusion: several gender-related differences were noted pertaining to the prevalence of and relationship between hyperuricemia , higher ALT, hypercholesterolemia, and hypertriglyceridemia and NAFLD in the present study.